Food security and hygiene practice among adolescent girls in Maiduguri Metropolitan Council, Borno State, Nigeria - Shapu, Ruth Charles; Ismail, Suriani; Ahmad, Norliza; Lim, Poh Ying; Njodi, Ibrahim Abubakar (Multidisciplinary Digital Publishing Institute, 2020)
Inadequate food security contributes to poor health outcome for all, including adolescent girls. The study aims at determining the level of food security and hygiene among adolescent girls. A school-based cross-sectional study was carried out among adolescent girls aged 10 to 19 years old from six schools in Maiduguri Metropolitan Council, Borno State. The instrument for data collection was a questionnaire using KoBoCollect Toolbox between June and July 2019. Multivariable logistic regression was used to identify the predictors of food security and hygiene among respondents. A majority of the respondents (73.5%) were in a very low food security level. Three factors were significantly associated with food security level, these included schools (p = 0.007), age of mother (p = 0.004), and occupation of mother (p < 0.001). School (p = 0.003), age (father p = 0.017; mother; p = 0.012), hygiene (p = 0.005), and occupation of mother (p = 0.002) were predictors of food security. About (46.6%) of respondents had poor hygiene practice, school (p = 0.016) was significantly associated with hygiene practice. School (p = 0.019; and p = 0.005) and food security (p = 0.009) were predictors of hygiene practice. This study reveals a high prevalence of low food security among adolescent girls.